Implementation of School-Based Management Committee of Public Secondary Schools in Nigeria: Contribution, Challenges and Way Forward - Niyi Jacob Ogunode; Okwuagwu Esther Chijindu (Researchparks Publishing, 2022)
School-Based Management Committee was introduced to Nigerian educational institutions especially the Basic schools and secondary schools with the aims of encouraging host community participation in the school administration and management. The implementation of the School-Based Management Committee of public secondary school in Nigeria is however faced with some problems. This paper examined the problems hindering the implementation of School-Based Management Committee of public secondary schools in Nigeria. The paper employed secondary and primary data. The data were sourced from print and online resources. The paper discovered that School-Based Management Committee of public secondary schools has contributed to the improvement of school administration and management, funds mobilization and improvement in planning and maintenance of school plant facilities. The paper also identified inadequate funding, corruption, insecurity, poor participation of parents, poor capacity building of stakeholders, lack of motor-able roads and ineffective supervision of the programme as the major problem hindering the implementation of school-based management committee of public secondary schools in Nigeria. The paper specifically suggested that the government should increase the funding of the programme and communities and parents should be encouraged to contribute their counterpart funding on time.